Amplitude estimating algorithm for single channel mixing signals - RUI Guo-sheng 1; XU Bin 2; ZHANG Song2 (Tongxin xuebao)
Aimed at non-cooperative communication situations an amplitude estimating question for single channel MSK mixing signals with the same modulating parameters was studied.Based on the derivation of cyclic spectrum for MSK mixture,amplitudes of mixing signals were estimated by searching high-intensity spectral lines along cyclic frequency axis at zero frequency.The envelop of leakage spectrum introduced by fast cyclic spectrum calculation was applied to eliminate the illegibility of spectral line selection.The envelop values of leakage spectrum located at high-intensity spec-tral lines were used to correct the corresponding amplitudes of cyclic spectrum in order to improve estimating accuracy.Simulation results show its good performance for mixing signals without large power difference when the SNR is greater than ?15dB.It is worthy for lower SNR applications without any prior information.